Michał Kalecki w polskiej i światowej ekonomii - Kowalczyk, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The article is devoted to the presentation of work and views of Michał Kalecki, one of the most important representatives of economic thought in the twentieth-century Poland. Kalecki tended to explain the mechanism of the cyclical fluctuations in the economy, to develop and to enrich the relevant theory. He proved the influence of capitalistic enterprises investment decisions and technological progress (innovations). The leading idea of his theory was the conviction that the problem of trade cycles is an important component of a more general theory of growth. His views on the causes of the cyclical fluctuactions were founded on a large socio-economic vision of the process of improving production, income and employment.
Keywords: Kalecki, Michał (1899-1970)